Interrogating the Neoliberal Lifecycle The Limits of Success - Clack, Beverley; Paule, Michele; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
In this timely collection, contributors from a number of disciplines discuss neoliberal visions of success, and the subsequent effects they have on the construction of the lifecycle. Frequently mentioned in popular political discourse, the notion of neoliberalism is often deployed as shorthand for the consensus that austerity is necessary and the hard-working individual can survive it. This volume unpicks and interrogates the term by engaging with the interface between the political ubiquity of neoliberal forms and its lived experience in neoliberal societies, cutting across a multiplicity of factors including gender, age, and access to education. Impressive in its wide scope and analysis, Interrogating the Neoliberal Lifecycle presents an informed discussion not only of the limits of the neoliberal paradigm but also of possible alternatives. .
Chapter 1. Introduction: Welcome to the Neoliberal Lifecycle!; Beverley Clack and Michele Paule -- Part 1: Childhood, Youth and Schooling. - Chapter 2: Personal Moral Autonomy, Responsibility and Choice: Do We Know What Our Cultural Discourses Are Doing to Young People's Mental Health?; Philippa Donald -- Chapter 3: Boys from the Bronx, Men from Manhattan: Gender, Aspiration and Imagining a (Neoliberal) Future After High School in New York City; Patrick Alexander -- Chapter 4: Girl Trouble: Not the Ideal Neoliberal Subject; Michele Paule. - Part 2: The University Under Neoliberalism -- Chapter 5: Paying for Success "Outside Your World": Antagonising Neoliberal Higher Education; Louise Livesey -- Chapter 6: Universities: The Neoliberal Agenda; Bob Brecher -- Part 3: Work, Success and Failure -- Chapter 7: Gender Equality, Austerity, Vulnerabilities and Resistance in the Spanish Neoliberal Lifecycle; Louise Grisoni and Sonia Ruiz -- Chapter 8: Towards a Manifesto: On the Love of Failure; Susan Crosier -- Chapter 9: "I Don't Want to Live Too Long!": Successful Ageing and the Failure of Longevity in Japan; Jason Danely. - Part 4: Death and Dying -- Chapter 10: Old Age and the Neoliberal Life Course; Susan Pickard -- Chapter 11: Death and Dying in "Third Way" Death Manuals: Shaping Life and Death after Neoliberalism; Beverley Clack -- Chapter 12: Afterword: Advice for a Life Beyond Neoliberalism?; Beverley Clack and Michele Paule. .
Keywords: Political sociology; Culture -- Study and teaching; Aging; Social policy; Political Sociology; Cultural Studies; Ageing; Social Policy